Diagnostic testing for chronic spontaneous urticaria with or without angioedema: The do's, don't and maybe's - Jonathan A. Bernstein, MD; Ignacio Ansotegui, MD, PhD; Riccardo Asero, MD; Aleena Banerji, MD; Stephen Betschel, HBSc, MD; Timothy Craig, DO; José Luis García-Abujeta, MD; René Maximiliano Gómez, MD, PhD; Anete S. Grumach, MD, PhD; Michihiro Hide, MD, PhD; David M. Lang, MD; Michael Levin, MD, PhD; et al. (World Allergy Organization Journal)
Chronic spontaneous urticaria (CSU), with or without angioedema, is heterogeneous and comprised of different endotypes and phenotypes. Because acute urticaria will mostly resolve spontaneously, routine testing and laboratory evaluation is not required unless supported by the clinical history or physical examination. With the advent of omalizumab, there has been a surge of interest in identifying biomarkers that could predict response to this treatment. In the process of investigating biomarkers as prognosticators, several CSU phenotypes and endotypes have emerged, which have made it evident that novel therapies targeting non-IgE mechanistic pathways are needed to control symptoms in patients unresponsive to the currently recommended therapies by the most recent international guidelines. The current data support peripheral eosinophils, autoantibodies against IgE or FcεRI α subunit measured by basophil histamine release assays, total IgE levels and IgG autoantibodies against thyroid peroxidase (TPO) as specific markers to differentiate type 1 autoimmune (autoallergic) CSU from type 2b autoimmune CSU before starting treatment especially with omalizumab. These markers have been included as exploratory endpoints in many clinical trials investigating novel therapies or for repurposing existing biologics to determine responders and non-responders, but these data are not completely clear at this time. Therefore, further randomized controlled studies and real-world studies are needed to demonstrate more conclusively the utility of ordering these tests in CSU patients when they initially present or when it is determined they are not responsive to high dose second generation H1-antihistamines (SGAH) before they can be included in evidence-based CSU guidelines. This review examines the value of obtaining diagnostic tests in the initial evaluation of CSU patients to predict treatment response.